Italian healthcare workers’ perspectives on strategies to enhance vaccination coverage: A national cross-sectional survey - Ricciardi, Giovanni Emanuele; Ancona, Angela; Cuciniello, Rita; Chiecca, Greta; Castagna, Antonella; Renzi, Cristina; Rezza, Giovanni; Moro, Matteo (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Healthcare workers (HCWs) are trusted advisors in vaccination promotion, yet little is known about which strategies they consider most effective. This study evaluated Italian HCWs’ preferences for vaccination promotion strategies across different professions and age groups. Methods: A cross-sectional survey was conducted among 3,000 HCWs (physicians, nurses, pharmacists, and midwives) in Italy between August and September 2025 using computer-assisted telephone interviews. Stratified quota sampling ensured representativeness by region, profession, and gender. Participants rated nine vaccination promotion strategies on a 10-point scale. Descriptive statistics and ANOVA were used to compare mean endorsement scores and endorsement rates (≥6/10) across professional categories and age groups. Results: All strategies received moderate to strong endorsement (mean scores 5.2-6.6). The two priority strategies were free pre-vaccination laboratory tests and paid time off for vaccination (6.6). Economic incentives (5.2) and improved scheduling access (5.3) received the lowest support. No significant differences emerged across professional categories or age groups, indicating remarkable consensus among HCWs. Discussion: Italian HCWs prioritize strategies addressing structural and psychological barriers over financial incentives. This consensus suggests policy makers should focus on competence-building, accessibility, and trust-enhancing interventions rather than economic approaches to improve vaccination coverage.